Comparative analysis of differential gene expression in the culms of sorghum - Ndimande, Gordon Sandile (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Genetics. Plant Biotechnology))--University of Stellenbosch, 2007.